2017
DOI: 10.1103/physrevb.96.054307
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of a composite quasiparticle by an impurity on a lattice

Abstract: We study scattering of a composite quasiparticle, which possesses a degree of freedom corresponding to relative separation between two bound excitations, by a delta-like impurity potential on a one-dimensional discrete lattice. Firstly, we show that, due to specific properties of their dispersion, lattice excitations bind to impurities with both negative and positive potentials. We demonstrate that the finite size of the composite excitation leads to formation of multiple excitation-impurity bound states. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Recently quantum tunneling of a composite object through a δ potential barrier has been studied in continuous space [6] and on a lattice [7]. It was found that its internal arXiv:1705.05426v3 [gr-qc] 24 Jan 2019 structure can produce phenomena such as long-lived resonances and bound states in the continuum that can not be seen in a single particle quantum tunneling.…”
Section: Introductionmentioning
confidence: 99%
“…Recently quantum tunneling of a composite object through a δ potential barrier has been studied in continuous space [6] and on a lattice [7]. It was found that its internal arXiv:1705.05426v3 [gr-qc] 24 Jan 2019 structure can produce phenomena such as long-lived resonances and bound states in the continuum that can not be seen in a single particle quantum tunneling.…”
Section: Introductionmentioning
confidence: 99%